Structured illumination approaches for super-resolution in plant cells. (8th October 2018) - Shaw, Sidney L; Thoms, David; Powers, James
Abstract : The application of structured illumination approaches for super-resolution light microscopy in plant cells is reviewed. Challenges and recent inroads using both wide-field and point-based techniques are discussed with specific application to live-cell imaging. Abstract: The advent of super-resolution techniques in biological microscopy has opened new frontiers for exploring the molecular distribution of proteins and small molecules in cells. Improvements in optical design and innovations in the approaches for the collection of fluorescence emission have produced substantial gains in signal from chemical labels and fluorescent proteins. Structuring the illumination to elicit fluorescence from specific or even random patterns allows the extraction of higher order spatial frequencies from specimens labeled with conventional probes. Application of this approach to plant systems for super-resolution imaging has been relatively slow owing in large part to aberrations incurred when imaging through the plant cell wall. In this brief review, we address the use of two prominent methods for generating super-resolution images in living plant specimens and discuss future directions for gaining better access to these techniques.